2007
DOI: 10.1097/psy.0b013e31805fe2bc
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Association Between Mixed Lateral Preference and PTSD: Confirmation Among a National Study of 2490 US Army Vietnam Veterans

Abstract: Our study confirmed findings reported among mostly smaller clinical samples and suggested that mixed lateral preference was associated with PTSD, especially among those individuals exposed to more severe psychological trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 25 publications
6
41
0
Order By: Relevance
“…In accordance with previous findings (Boscarino & Hoffman, 2007;Chemtob & Taylor, 2003;Spivak et al, 1998), a negative correlation was found between PTSD symptoms severity and the degree of lateral preference in overall population of the current study. Further analyses indicated that the pattern of the relationship between PTSD symptoms and lateral preference altered between participants with low, moderate and high Moral Objection.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In accordance with previous findings (Boscarino & Hoffman, 2007;Chemtob & Taylor, 2003;Spivak et al, 1998), a negative correlation was found between PTSD symptoms severity and the degree of lateral preference in overall population of the current study. Further analyses indicated that the pattern of the relationship between PTSD symptoms and lateral preference altered between participants with low, moderate and high Moral Objection.…”
Section: Discussionsupporting
confidence: 94%
“…It has been suggested that mixed handedness might only be a limited index for mixed cerebral lateralization (Boscarino & Hoffman, 2007). However, our findings of a relationship between PTSD severity and mixed handedness are in line with previous reports among other diverse populations (Boscarino & Hoffman, 2007;Chemtob et al, 2006;Chemtob & Taylor, 2003;Saltzman et al, 2006;Spivak et al, 1998).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Ηοwever, as indicated by Dragovic (2004), the majority of existing handedness questionnaires lack valid criteria for partitioning the continuous measure into a small number of handedness classes. That is the reason why researchers (e.g., Boscarino & Hoffman, 2007;Giotakos, 2001;Taylor, Dalton, Fleminger, & Lishman, 1982) sometimes use more than one criterion to test the stability of their findings or allow comparability with similar studies. To overcome this methodological problem, the present study evaluated the association between lateral preference for handedness and developmental dyslexia using both continuous and several dichotomous classifications of hand preference.…”
Section: Introductionmentioning
confidence: 99%